Enhancing Efficiency and Reliability of Tidal Stream Energy Conversion through Swept-Blade Design - Yangyang Zheng; Wenxian Yang; Kexiang Wei; Yanling Chen; Hongxiang Zou (Energies, 2024)
The current limited efficiency and reliability of tidal current turbines (TCTs) have posed significant challenges in effectively harnessing tidal stream energy. To address this issue, this paper undertakes both numerical and experimental studies to explore the advantages of swept blades over conventional straight blades in terms of energy capture efficiency and cavitation resistance. It is found that both the sweep length and sweep angle of the blade can influence the power generation efficiency of the TCT. For the particular swept blade investigated in this study, the highest power coefficient is achieved when the sweep length is 0.544 m and the sweep angle is 28.88°. The research also demonstrated that the swept-blade TCT shows a higher power generation efficiency than the straight-blade TCT across a broad range of rotor speeds. To be precise, with the swept blades, the power coefficient of the TCT can be improved by 5–17%, depending on the tip speed ratio. Additionally, swept blades exhibit a superior cavitation resistance. This is evidenced by their higher cavitation numbers across all tip speed ratios in comparison to conventional straight blades.